Convenient Solutions to an Inconvenient Truth : Ecosystem-based Approaches to Climate Change - World Bank (World Bank, 2012)
The World Bank's mission is to alleviate poverty and support sustainable development. Climate change is a serious environmental challenge that could undermine these goals. Since the industrial revolution, the mean surface temperature of earth has increased an average 2 degree Celsius due to the accumulation of greenhouse gases in the atmosphere. Most of this change has occurred in the past 30 to 40 years, and the rate of increase is accelerating. These rising temperatures will have significant impacts at a global scale and at local and regional levels. While it remains important to reduce greenhouse gas emissions and reverse climate change in the long run, many of the impacts of climate change are already in evidence. As a result, governments, communities, and civil society are increasingly concerned with anticipating the future effects of climate change while searching for strategies to mitigate, and adapt to, its current and future effects. Global warming and changes in climate have already had observed impacts on natural ecosystems and species. Natural systems such as wetlands, mangroves, coral reefs, cloud forests, arctic and high latitude ecosystems are especially vulnerable to climate-induced disturbances. Current efforts to address climate change focus mainly on reducing emissions of greenhouse gases, mainly through cleaner energy strategies, and on attempting to reduce vulnerability of communities at risk by improving infrastructure to meet new energy and water needs. This report attempts to set out a compelling argument for including ecosystem-based approaches to mitigation and adaptation as a third and essential pillar in national strategies to address climate change. The report is targeted at both Bank task teams and country clients. Such ecosystem-based strategies can offer cost-effective, proven and sustainable solutions contributing to, and complementing, other national and regional adaptation strategies.